Effect of Phytic Acid on the Texture of Tofu and the Precipitaion Reaction in Tofu Making - Agus Setyono (Indonesian Association of Food Technologists, 1994)
Soybean curd or tofu is widely used as daily foods by people in Indonesia. One of the delicate steps in the preparation of tofu is the addition of a salt to precipitate soy protein. The common salt of calcium sulfate and the peeled soybeans were used to produced the non phytic acid soybean milk. Futhermore the adjustment of phytic acid content in soybean milk was done by addition of phytic acid. The result showed that phytic acid is the most important factor in the formation of precipitated protein aggregate in tofu at above isoelectric point. Weight and moisture content werw affected by both phytic acid and amount of calcium sulfate as a coagulant. The results may conclude that either natural phytic acid present in soybean seeds or phytic acid added to soybean milk, have a significant effect on the texture of tofu. The higher the phytic acid content in soybean milk is the stronger the interaction among soybean protein, calcium and phytic acid. This is important in producing tofu of desirable hardness.